Corporate Social Responsibility and other factors affecting Tax Avoidance - Venezya, Venny; Juwono, Arleen Herawaty (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The primary objective of this research is to obtain empirical evidence for the influence of corporate social responsibility (CSR) and other factors including return on asset, leverage, sales growth, capital intensity ratio, inventory intensity ratio, firm size, financial distress, accounting conservatism on tax avoidance. Population used in this research are consumer non-cyclicals and consumer cyclicals companies listed on the Indonesian Stock Exchange (IDX) from 2020 to 2022. The study employs a purposive sampling technique with the final result meeting the criteria on 62 companies, 186 data over a three-year period from 2020 to 2022. This research used multiple regression method to analyze the data. The results reveal that return on asset, sales growth, and inventory intensity ratio influence tax avoidance. On contrary, leverage, capital intensity ratio, firm size, financial distress, accounting conservatism, and corporate social responsibility show no influence on tax avoidance. Depending on the amount of profitability the business experiences, it will decide what steps to take to maximize its net profit. In other side, companies that incur costs that can be counted as tax deductions feel that the company no longer needs to avoid taxes.